Women’s Reproductive Rights in the Practice of ‘Azl: A Comparative Analysis of Islamic Legal Schools and Indonesian Islamic Family Law - Khairatun Nisa; Imam Yazid; Tetty Marlina Tarigan (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2026)
The practice of ‘azl (coitus interruptus) remains a significant issue in Islamic family law because it concerns not only birth control but also reproductive authority and spousal rights within marriage. This article examines the position of the wife’s consent in the practice of ‘azl through a comparative analysis of the four major Sunni legal schools and evaluates its relevance to Indonesian Islamic family law. Employing normative legal research with statutory, conceptual, and comparative madhhab approaches, the study analyzes classical juristic texts, Islamic legal principles, and Indonesian family law regulations. The findings reveal that the Mālikī and Hanbalī schools require or strongly emphasize the wife’s consent, while the Shāfi‘ī and Ḥanafī schools provide broader authority to the husband despite acknowledging the wife’s reproductive interests. Through the frameworks of maqāṣid al-sharī‘ah and mubādalah, the study argues that reproductive decisions should be based on mutual consultation and shared responsibility. The article concludes that recognizing the wife’s consent strengthens reproductive justice and provides a normative foundation for the future development of Indonesian Islamic family law.